Bulgaria : Second Review Under the Stand-By Arrangement and Request for Waiver of Applicability of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines Bulgaria's Second Review Under the Stand-By Arrangement (SBA) and a Request for Waiver of Applicability of Performance Criteria. Over the last six-month period, Bulgaria's macroeconomic stability has strengthened further. However, political pressures have made it more challenging to maintain a prudent and flexible fiscal policy and have weakened the momentum of structural reforms. Bulgaria has had a commendable performance in 2002, and the IMF staff supports the authorities' request to complete the second program review under the SBA.